2018
DOI: 10.1021/acsami.8b19425
|View full text |Cite
|
Sign up to set email alerts
|

A Stretchable Strain-Insensitive Temperature Sensor Based on Free-Standing Elastomeric Composite Fibers for On-Body Monitoring of Skin Temperature

Abstract: To realize the potential applications of stretchable sensors in the field of wearable health monitoring, it is essential to develop a stable sensing device with robust electrical and mechanical properties in the present of varying external conditions. Herein, we demonstrate a stretchable temperature sensor with the elimination of strain-induced interference via geometric engineering of the free-standing stretchable fibers (FSSFs) of reduced graphene oxide/ polyurethane composite. The FSSFs were formed in serpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 46 publications
1
115
0
1
Order By: Relevance
“…The sensor was reproducible with the cycling temperature changes, indicating reliable and stable performances in repeated measurements. The response and recovery time of the sensor were about 4.5 and 12.5 s, respectively, calculated with an exponential fitting model (Figure f) . To test the long‐term stability, the UCNPs‐SPOFs sensor was kept at a constant temperature of 30 °C and the emission spectra were recorded for 4 days ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor was reproducible with the cycling temperature changes, indicating reliable and stable performances in repeated measurements. The response and recovery time of the sensor were about 4.5 and 12.5 s, respectively, calculated with an exponential fitting model (Figure f) . To test the long‐term stability, the UCNPs‐SPOFs sensor was kept at a constant temperature of 30 °C and the emission spectra were recorded for 4 days ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…To meet the requirements of these applications, wearable sensors are required to be flexible, stretchable, and biocompatible so that they can stretch, bend, and twist like skin in long‐term wearing. As such, there has been considerable effort in developing various stretchable materials and structures to achieve a range of wearable devices for monitoring temperature, strain, pressure, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the PTL/rGO hybrid coatings shows a negative temperature coefficient behavior (Figure S9, Supporting Information), which indicated that conductivity modulation of the rGO nanosheets with temperature changes is a dominant mechanism rather than conductivity modulation induced by the thermal expansion of the protein matrix. [ 49 ] The high‐conductivity rGO nanosheets enclosed by the hygroscopic protein aggregation network provide a sensitive platform to sense a series of stimuli, typically including moisture and related human breathing monitoring (Figures S10 and S11, Supporting Information), and strain/pressure and related Morse code information transmission (Figure S12, Supporting Information). Unlike pristine rGO, generally having poor biocompatibility, [ 50 ] the protein component endowed the PTL/rGO hybrid coating with good biocompatibility, so that the adhesion and proliferation of HMEC‐1 endothelial cells, a commonly used cell line, on the hybrid coating were much better than those on the pristine rGO film (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…They can be sewn into regular fabrics to measure the temperature in different parts of the body or attached to a bandage (Figure h). Through geometric engineering, it is possible to minimize the interference of strain on the temperature response …”
Section: Applicationsmentioning
confidence: 99%
“…Flexible sensors are especially suited for novel applications in healthcare, which are represented by noninvasive, measurement and real‐time monitoring of biophysical and biochemical signals from the human body, such as wrist pulse monitoring, strain measurement, humidity measurement, vibration detection, touch and pressure measurement, electrochemical detection, body temperature measurement, and many others. Table shows the flexible sensors, materials used, their performance, and applications.…”
Section: Introductionmentioning
confidence: 99%